Influence of rice variety and plant spacing on weed suppression under aerobic condition - Sunyob, Norhidayati (2013)
This study comprised of two sets of experiments. The plant house and field trials were conducted at MARDI Bertam Rice Research Station in Seberang Perai, Penang. First experiment was conducted in plant house and it was repeated in the field. The second experiment which also repeated was conducted both at experimental field. These studies began in December 2008 and ended in March 2011. Weeds are the greatest constraint in aerobic rice cultivation due to lack of water standing to suppress weed. Therefore, by adoption of competitive rice varieties and the optimum plant spacing could reduce yield losses due to weed competition. The objectives of the first experiment were to evaluate the competitive ability of five rice varieties (AERON 1, AERON 4, M9, MR211 and MR 220CL2) against weeds under aerobic rice systems, and thus determining the suitable variety for aerobic rice cultivation. The above five rice varieties were evaluated to determine their performance under two weeding regimes (weedy and weed free condition). The experimental units were kept unweeded (weedy treatment) and weed free (weed free treatment) throughout the growing season. Manual weeding and the application of recommended herbicides (Sofit and Satunil) were conducted to control weeds in weed free treatments. AERON 1 had resulted in the lowest weed dry weight and weed density while the highest was observed in MR211, in both plant house and field experiments. Sixteen weed species had infested the experimental unit in the plant house and field experiments. In weed composition, the sum dominance ratio (SDR) value showed that grasses infested at the highest percentage as compared to those of sedges and broadleaves (resulted in minor infestation). Leptochloa chinensis was the most dominant weed in plant house while in field was Echinochloa colona. Weed competition gave negative effect on selected parameters of growth and development [plant height, tiller number and SPAD value],grain yield and yield components (filled grain panicle-1, sterility percentage and thousand grain weight). AERON 1 produced the highest grain yield which 2.02 t ha-1 and 1.79 t ha-1 in plant house and field experiment, respectively while MR211 produced the lowest yield. The yield production of M9, MR220 MCL2 and especially MR211 were adversely affected by weeds and possibly by aerobic condition. Relative yield loss was higher in plant house (57.1 % to 74.8%) as compared to those in the field (53.1% to 70.9%). The lowest percentage relative yield loss was obtained at AERON 1 and this showed that AERON 1 was the most competitive variety against weeds as it yielded the lowest weed dry weight (better weed suppressive ability) and relative yield loss (weed tolerance) and it had high grain yield. The objective of second experiment was to determine the best plant spacing to achieve maximum yield and better weed suppression under aerobic condition. From previous study, AERON 1 had been chosen as planting material as it produced the highest grain yield and the lowest relative yield loss. The second experiment consist of five plant spacing namely 10 x 10 cm, 15 x 15 cm, 20 x 20 cm, 25 x 25 cm and 30 x 30 and was repeated in the second trial with the slightly modification of treatment with spacing of 15 x 15 cm, 15 x 20 cm, 20 x 20 cm, 20 x 25 cm and 25 x 25 cm. Both trials were tested under two weeding regimes (weedy and weed free condition). The lowest weed dry weight was produced by the closest plant spacing (10 x 10 cm in first trial and 15 x 15 cm in second trial). Similar pattern was observed in weed density (no. m-2). Grasses was the most dominant weeds in both trials, followed by sedges and with smaller amount of broadleaves. In the first trial, rice field was infested with 12 weed species with the most dominant weed was Echinochloa colona. The second trial was dominanted by Leptochloa chinensis with 22 weed species observed. Mean of grain yield was highest at closest spacing of 10 x 10 cm (2.55 t ha-1) in first trial, and in the second trial was 1.85 t ha-1 of yield in 15 x 15 cm spacing. Relative yield loss due to weed competition was ranging from 36.1 % to 54.9 % in the first trial, and with the range of 50.7% to 57.2% in the second trial. The best plant spacing suggested from this study was 10 x 10 cm spacing or 15 x 15 cm for higher yield and better weed suppression.